الكلمات الجاوية ذات أصل قرآني في كتاب الإبرز لمعرفة القرآن العزيز والاستفادة منها في تعليم اللغة العربية للجاويين - Muhammad Fadhil (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2019)
Many Javanese Vocabularies are used in the Javanese community in its daily conversation and concept. Basically words that are taken for the Al-Quran, from this point, this research aims to point out the Javanese Vocabulary that originates from the Al-Quran and is also aimed to show how to use these words in teaching Arabic in the Javanese community.The researcher used the analytical descriptive method, whith this method the researcher gathered and analysed fifty four Javanese words that originated from Al-Quran from chapter 3 until 8 from Kitab Al Ibriz Li Marifati Al-Quran Al-Aziz, then the researcher classified these words into 4 parts based on the change of new meanings after entering the Javanese language namely: 1). Arabic Vocabulary that contains the same meaning in Javanese language. 2). Arabic Vocabulary that has a narrowed meaning in Javanese language. 3). Arabic Vocabulary that experience an expansion of meaning in Javanese language. 4). Arabic Vocabulary that undergoes a change of meaning in Javanese language.This essay shows that the Javanese words taken from the Al-Quran is able to be used in teaching Arabic to the Javanese by making reading materials conversations, writing sentences and making exam questions aimed to know the student’s understanding.